2008 IEEE/AIAA 27th Digital Avionics Systems Conference 2008
DOI: 10.1109/dasc.2008.4702817
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Departure Route Planning

Abstract: This paper describes research on the Integrated Departure Route Planning (IDRP) operational concept and supporting functions that will assist Traffic Flow Management (TFM) personnel conducting departure management. IDRP will provide automated support and information to help decision makers evaluate and implement different solutions, taking into account all significant data such as filed flight plans and acceptable alternatives, surface departure queues, predicted convective weather and traffic congestion impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Previous research [1] identified two significant challenges facing today's departure and arrival traffic management system. The first challenge is the lack of integrated information presented to decision makers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research [1] identified two significant challenges facing today's departure and arrival traffic management system. The first challenge is the lack of integrated information presented to decision makers.…”
Section: Introductionmentioning
confidence: 99%